Tahap keprihatinan alam sekitar dan amalan kepenggunaan hijau pengguna di Petaling Jaya, Selangor - Sabri, Mohamad Fazli; Teoh, Yong Yong (Universiti Putra Malaysia Press, 2006)
This research was conducted to study the level of environmental concern and practices in green consumerism among consumers in Petaling Jaya, Selangor. A total of 80 working adults at Schmidt BioMedTech Sdn. Bhd. were selected as respondents using systematic sampling method. Data were collected through a self-administered questionnaire. Data collected were analysed using 'SPSS for Windows'. More than 70% respondents have high level of environmental concern but moderate level of green consumerism practices. Most of the respondents use green products occasionally and their main sources of information of such products come from newspaper and television. The study also revealed that in general the consumers have positive perceptions on green products. The findings showed that there is a positive and significant relationship between the level of environmental concern and practices in green consumerism (r=0.301, p≤0.01). This indicates that the higher the level of environmental concern, the higher the level of practices in green consumerism among consumers. However, the findings also showed that there is considerable discrepancy between level of environmental concern and level of green consumerism practices. The implication of the study showed that coordinate effort should be taken by various agencies such as government, consumers, business organizations, consumer groups and other nongovernmental organizations to enhance sustainable practices among Malaysian consumers.